The structure of socio-economic metabolism and its drivers on household level in Hungary. (20th January 2018) - Dombi, Mihály; Karcagi-Kováts, Andrea; Tóth-Szita, Klára; Kuti, István
Abstract: The joint examination of input flows and the stocks of households provides novel perspectives for socio-economic metabolism (SEM) research. Our study aims to compare household level material flows and stocks, and economy-wide material inputs, and to explore influential factors affecting the level of metabolism at household level. Household diaries and inventories (n = 73) were used to assemble household-level data regarding material flows and stocks. The mean value of the extrapolated annual material inputs 2.16 tons per household member, while household stocks represented 1.17 tons per household member excluding building stocks, and 46 tons if buildings were considered in the estimation. According to our results, material inputs and stocks are depending on household size and income exclusively. Amount of the direct input flows of the economy exceed the direct input flows of households significantly. Household inputs represent 10.3% of the Hungarian direct material consumption (DMC). For better understanding, the material balance of Hungary was compiled and extended using an additional layer of the flows' functions. With regard to input flows, every increment in direct inputs evokes multiple increment on macroeconomic scale. Since several input flows are assumed to be driven by the amount of stocks, an increment in material stocks will add further material consumption surplus to this effect. Improvements in production processes can narrow multiplicative effects especially in food supply chains and construction activity. Similar characteristics in material flow and stock relations of three countries (Japan, Germany and Hungary) highlight that the decoupling is not possible without accumulation of lower amount of material in the societies. Highlights: Material inputs per household member approach 2.2 tones, with a high portion of fossil fuels. Stocks per household member exceed one ton, and 44 tones if buildings are considered. Household stocks and flows depend on household size and income significantly. Materials used directly by the households were estimated to be 10.3% of economy-wide input.